Cobalt vanadium layered double Hydroxide/FeOOH heterostructure catalyst with strong electron interactions for stable oxygen evolution performance. (October 2021) - Wang, Zhipeng; Chen, Liang; Xu, Shoudong; Zhang, Ding; Zhou, Xianxian; Wu, Xu; Xie, Xianmei; Qiu, Xiangyun
Abstract: The oxygen evolution reaction (OER) is considered the bottleneck for the water-splitting process, due to its high activation barrier. Therefore, developing efficient and low-cost electrocatalysts to enhance sluggish kinetics remains a challenge. As an admittedly promising candidate catalyst for the OER, layered double hydroxides (LDHs) are limited by weak conductivity and poor activity sites. Herein, an interface engineering strategy was utilized to increase the intrinsic activity of CoV-LDHs by coupling with FeOOH via a novel and inexpensive protocol. The hybrid catalyst CoV-LDHs@FeOOH/NF showed a low overpotential of 232 mV at a current density of 10 mA cm −2, with a low Tafel slope of 16.7 mV dec −1 in a 1 M KOH aqueous solution, which is superior to that obtained for the individual CoV-LDHs/NF and FeOOH/NF counterparts. The enhanced OER activity mainly benefits from the electronic exchange among Co 2+, V 3+, and Fe 3+ . In addition, the heterostructure shows excellent catalytic durability of approximately 100 h. This work provides a novel method to synthesize V-based LDH materials and an excellent electrocatalyst for improving OER activity. Graphical abstract: Image 1 Highlights: V-based LDHs was synthesized with NH4 VO3  as the vanadium source via a chemical reduction protocol. The CoV-LDH@FeOOH composite catalyst delivered a high electrocatalyst performance and a stable durability The heterogeneous catalyst CoV-LDH@FeOOH showed excellent OER performance due to the charge redistribution of 3d metals.